2020
DOI: 10.3389/fpubh.2020.00259
|View full text |Cite
|
Sign up to set email alerts
|

How Are We Facing It? Dispatches From Pathology Residents in a COVID-19 Lombardy Hospital

Abstract: At the end of February, the Italian National Health Service reported a hot spot of Coronavirus disease in the Lombardy region. COVID-19 is a highly pathogenic viral infection which poses some challenges for healthcare workers. Indeed, Pathology Departments are involved in reorganizing samples' management, from their delivery until their processing, according to National and WHO guidelines. Since Lombardy has been declared COVID-19 hot spot, due to decreasing number of surgical procedures, our Department adopte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
5

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 2 publications
0
5
0
5
Order By: Relevance
“…One of the consequences of the COVID-19 crisis was the absolute necessity to develop virtual educational programs, notably for residents and junior pathologists (digital pathology training, virtual courses, webinars, etc.). 28 , 29 , 30 However, the results of the present survey showed that only around 25% of the laboratories set up these programs, highlighting the urgent need to become aware of the utility of these different tools. In addition, some information, in particular concerning the biosafety procedures to follow in a pathology laboratory should be established through virtual training, and this was the case in the present study for no more than 25% of the laboratories.…”
Section: Discussionmentioning
confidence: 80%
“…One of the consequences of the COVID-19 crisis was the absolute necessity to develop virtual educational programs, notably for residents and junior pathologists (digital pathology training, virtual courses, webinars, etc.). 28 , 29 , 30 However, the results of the present survey showed that only around 25% of the laboratories set up these programs, highlighting the urgent need to become aware of the utility of these different tools. In addition, some information, in particular concerning the biosafety procedures to follow in a pathology laboratory should be established through virtual training, and this was the case in the present study for no more than 25% of the laboratories.…”
Section: Discussionmentioning
confidence: 80%
“…Permitiu-se então que os patologistas trabalhassem de forma remota durante a pandemia. A equipe de patologia recebeu um treinamento específico para aderência às novas normas, para que remodelassem sua rotina diária, mantivessem distâncias seguras, com isso a vida diária desses profissionais mudou drasticamente 20 .…”
Section: Resultsunclassified
“…Como consequência, foi implementada a patologia digital, que anteriormente era usada apenas para fins de pesquisa e a partir da pandemia foi introduzida para treinamento de residentes em histopatologia, aulas virtuais de citologia, quadros de tumores multidisciplinares e reuniões interinstitucionais 20 .…”
Section: Resultsunclassified
See 2 more Smart Citations